Eksistensi Radio Komunitas Kampus Surabaya di Era Konvergensi Media - Rozaqul Arif; Syaifudin Zuhri; Suwatah Suwatah (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2022)
Campus community radio in Surabaya over the past 20 years has thrived. This study discusses the existence of campus community radio in Surabaya which is incorporated in the Surabaya Campus Radio (RKS) forum in the era of media convergence. This research method uses a descriptive qualitative approach. The results of the study have revealed that the existence of campus radio in Surabaya is more widely used for developing interests, talents, and training in broadcasting or for laboratory purposes. Many campus radio broadcasts use streaming technology via the internet and as content service providers or over the top. Meanwhile, the migration of frequency-based analogue radio to digital or streaming platforms, as a solution to limitations of frequency, in terms of broadcast program aspects, is feasible for migration. This is because through broadcast programs owned by campus community radio will be more competitive, because the digital techniques can encourage the growth of convergence which is beneficial for audiences not only to listen but they are also able to interact and discuss with topics as well as express opinions, so that they can meaningfully contribute to the programming